A Divide & Conquer Approach to Leads-to Model Checking. (1st February 2021) - Phyo, Yati; Minh Do, Canh; Ogata, Kazuhiro
Abstract: The paper proposes a new technique to mitigate the state explosion in model checking. The technique is called a divide & conquer approach to leads-to model checking. As indicated by the name, the technique is dedicated to leads-to properties. It is known that many important systems requirements can be expressed as leads-to properties, thus it is worth focusing on leads-to properties. The technique divides an original leads-to model checking problem into multiple smaller model checking problems and tackles each smaller one. We prove a theorem that the multiple smaller model checking problems are equivalent to the original leads-to model checking problem. We conduct two case studies demonstrating the power of the proposed technique.